2004
DOI: 10.1243/095440504772830156
|View full text |Cite
|
Sign up to set email alerts
|

Laser milling as a ‘rapid’ micromanufacturing process

Abstract: Laser milling involves applying laser energy to remove material through ablation in a layer-by-layer fashion. Computer numerical control (CNC) programs for laser milling are obtained directly from a three-dimensional computer aided design (CAD) model of the workpiece. Thus, apart from being a material removal rather than a material accretion system, a laser milling machine operates like any other layered manufacturing technology equipment. This paper reviews the physical phenomena underlying the interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 6 publications
0
29
0
1
Order By: Relevance
“…Laser milling can be used to structure parts in a wide range of materials directly from CAD data via a layer by-layer machining strategy (Pham, Dimov, Ji, Petkov, & Dobrev, 2004). Material removal occurs as a result of laser irradiation and depending on the laser source and the workpiece, the ablation can take place through melting and ejection or sublimation .…”
Section: Laser Machiningmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser milling can be used to structure parts in a wide range of materials directly from CAD data via a layer by-layer machining strategy (Pham, Dimov, Ji, Petkov, & Dobrev, 2004). Material removal occurs as a result of laser irradiation and depending on the laser source and the workpiece, the ablation can take place through melting and ejection or sublimation .…”
Section: Laser Machiningmentioning
confidence: 99%
“…Laser milling is mostly used for machining parts from one side only. However, complete laser milling of parts is also possible, but it is necessary to address the accuracy issues associated with the re-positioning of the workpiece, which are common process design concerns when more than one machining setup is necessary (Pham et al, 2004).…”
Section: Laser Machiningmentioning
confidence: 99%
“…Laser micro-machining is primarily used for drilling, cutting, and milling. Specially, laser micro-milling is gradually gaining recognition as an important micromanufacturing technology in rapid prototyping, component miniaturization for different applications, and serial production of micro-devices by batch fabrication methods [71,73].…”
Section: Laser Micro-machiningmentioning
confidence: 99%
“…Thus, laser micro-milling using ultrashort pulses can improve surface quality. Pham et al [73] investigated laser micro-milling for machining ceramic micro-components; they demonstrated that laser micromilling with microsecond pulses can machine microcomponents with feature sizes as small as 40 mm. However, their investigation was still in its infancy and did not reveal the material removal mechanism and the interactions between the laser beam and the workpiece involved in the machining process.…”
Section: Laser Micro-machiningmentioning
confidence: 99%
“…However, silicon molds are not feasible for mass production purpose as they can break easily due to their inherent brittleness when there is slight misalignment of mold and substrate. As an alternative, strong and tough metallic molds with longer lifespan can be fabricated by high precision micromachining (micromilling [5,6], micro electrical discharge machining (μEDM) [7,8], laser micromachining [9][10][11], and micro electro chemical micromachining (μECM) [12]); lithography, galvanoforming, and plastic molding (LIGA) [13]; or by cold and superplastic embossing [14]. The surface finish of molds manufactured by micromilling and μEDM methods is relatively higher than that by the lithography method (0.3 μm for micromilling and 0.4-0.5 μm for μEDM [15]).…”
Section: Introductionmentioning
confidence: 99%